Artificial Heart Neural Networks - Satish Gajawada; Hassan M. H. Mustafa (Twenty Second Century Artificial Intelligence, 2021)
Artificial Neural Networks (ANN) is an interesting subject of study. The Human Brain was the inspiration for the ANN discipline. Humans’ hearts and brains are critical for their survival. Many articles have been written by researchers who place a high value on the brain. However, scientists haven’t done much research on the Heart, which is an important part in addition to the Brain. By integrating the notion of "Heart" into Artificial Neural Networks, the primary goal of writing this article is to present a path to ANN area Research Scientists. In this study, we coined and defined the term "Artificial Heart Neuron," which, along with Artificial Neuron, is the foundation of the Artificial Heart Neural Networks Field (AHNN Field). This piece is inspired by both the heart and the brain.